Visual Morbidity And Its Rehabilitation In Ocular Leprosy - Keshri Pradip Kr; Pathak Ashok; Kar H K; Malik P K; Sinha T R D; Sharma Suresh K (Wolters Kluwer Medknow Publications, 2002)
Five hundred and thirty-three cases of different types of leprosy with varying duration of disease and treatment were studied for the visual status before and after treatment. Final correct visual acuity was analysed with respect to the cause, the duration and the treatment undertaken. Leprosy is an important cause of ocular morbidity and blindness and the importance of early intervention and proper health serviced for rehabilitation is stressed.